2022
DOI: 10.3390/biom12030358
|View full text |Cite
|
Sign up to set email alerts
|

Anti-GD2 Directed Immunotherapy for High-Risk and Metastatic Neuroblastoma

Abstract: Neuroblastoma is one of the few childhood cancers that carries a tumor-specific antigen in the form of a glycolipid antigen known as GD2. It has restricted expression in normal tissue, such as peripheral afferent nerves. Monoclonal antibodies targeting GD2 have been applied clinically to high-risk neuroblastoma with significant success. However, there are different anti-GD2 products and administration regimens. For example, anti-GD2 has been used in combination with chemotherapy during the induction phase or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 96 publications
0
18
0
Order By: Relevance
“…Studies have shown that vaccineinduced antibodies, and/or therapeutic mAbs could induce ADCC against CNS cancers both in vitro and in vivo. [31][32][33][34] In particular, anti-GD2 antibodies with major antineuroblastoma mechanisms of ADCC, [35][36][37] could improve the cure rate of metastatic CNS neuroblastoma 38 and have been applied effectively to high-risk neuroblastoma. For RABV, it has been reported that the protective activity of a particular RABV mAb in vivo did not correlate with its virusneutralizing activity in vitro, 39 indicating that Fc effector functions may contribute to protection effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that vaccineinduced antibodies, and/or therapeutic mAbs could induce ADCC against CNS cancers both in vitro and in vivo. [31][32][33][34] In particular, anti-GD2 antibodies with major antineuroblastoma mechanisms of ADCC, [35][36][37] could improve the cure rate of metastatic CNS neuroblastoma 38 and have been applied effectively to high-risk neuroblastoma. For RABV, it has been reported that the protective activity of a particular RABV mAb in vivo did not correlate with its virusneutralizing activity in vitro, 39 indicating that Fc effector functions may contribute to protection effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of human effector cells, including peripheral blood nuclear cells and granulocytes from healthy human donors, dinutuximab beta was found to mediate the lysis of human NB and melanoma cell lines in a dose-dependent manner (Fig. 1 ) [ 15 , 16 ].
Fig.
…”
Section: Dinutuximab Betamentioning
confidence: 99%
“…(4) Monoclonal antibodies such as anti-GD2 can induce calreticulin (‘eat me’ molecule) expression on neuroblastoma cells and enhance phagocytosis by macrophages. The figure was created using Biorender.com, and was adapted from Chan and Chan [ 16 ]. CDC complement-dependent cytotoxicity, NK natural killer, ADCC antibody-dependent cellular cytotoxicity, ADP antibody-dependent phagocytosis …”
Section: Dinutuximab Betamentioning
confidence: 99%
“…3,4 In high-risk NB patients, anti-GD2 mAbs such as naxitamab induce antibody-dependent cellmediated cytotoxicity (ADCC). However, the overall success of anti-GD2 mAb immunotherapy for NB is highly dependent on the antitumor activity of natural killer (NK) and other effector cells, 5,6 and failure to respond to treatment can be attributed to NB cell resistance 7 or the inability of effector cells to kill tumor cells. 8,9 As a result, the long-term efficacy of anti-GD2 mAb immunotherapy is unveried, and there is a pressing need for novel strategies to overcome resistance.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 As a result, the long-term efficacy of anti-GD2 mAb immunotherapy is unveried, and there is a pressing need for novel strategies to overcome resistance. 7 It has been established that high-risk NB patients with increased RNA signatures for activated NK cells and CD8 + T cells experience improved outcomes. 10 This implies that agents that prevent down regulation of immune function in the tumor microenvironment could represent a strategy for overcoming resistance to immunotherapy in NB and other cancers.…”
Section: Introductionmentioning
confidence: 99%